Influence of potassium carbonate (K2CO3) as catalyst on biocrude oil yield and properties via hydrothermal liquefaction of Spirulina - Chao, Cherry Lyn V.
This study is relevant to developing biomass, specifically microalgae, as a source for a biofuel production through hydrothermal liquefaction (HTL). Hydrothermal liquefaction (HTL) is a thermochemical conversion that requires no drying of the feedstock because the whole microalgae biomass is decomposed and converted in hot compressed water. A biocrude oil is obtained as the main product, along with gaseous, aqueous and solid by-products. It was observed in different studies that catalysts, particularly alkali catalysts, improved liquefaction efficiency. This study investigated the effects of potassium carbonate (K2CO3) on the yield and properties of biocrude oil. Different amounts of catalysts used were 5,7.5, and 10 wt. % respectively. Biocrude oil was produced from hydrothermal liquefaction of Arthrospira platenis (formerly referred to as Spirulina platensis) in a micro-reactor at 280 and 350 degrees Celsius for two levels of residence time, 15 and 45 minutes. The biocrude produced under these different conditions were analyzed for C,H,N, and N content. Biocrude oil yield and its calorific value were also determined. The highest biocrude oil yield with catalyst (32.18 wt. %) was obtained at 280°C with 15 minutes residence time and 5 wt. % K2CO3. Highest HHV of 39.17 MJ/kg was obtained with the addition of 10 wt. % K2CO3 at 280°C and 45 minutes residence time. Biocrude oil obtained from the experiment runs had almost similar H/C, and O/C values to that of biodiesel and plant oil and was better than biomass pyrolysis oil. The N/C ratios of biocrude oil ranged between 0.03 to 0.09 with a starting N/C ratio of 0.17.